Behavioral health providers' perspectives of delivering behavioral health services in primary care: a qualitative analysis - Beehler Gregory P; Wray Laura O (BMC, 2012)
Abstract Background Co-located, collaborative care (CCC) is one component of VA's model of Integrated Primary Care that embeds behavioral health providers (BHPs) into primary care clinics to treat commonly occurring mental health concerns among Veterans. Key features of the CCC model include time-limited, brief treatments (up to 6 encounters of 30 minutes each) and emphasis on multi-dimensional functional assessment. Although CCC is a mandated model of care, the barriers and facilitators to implementing this approach as identified from the perspective of BHPs have not been previously identified. Methods This secondary data analysis used interview data captured as part of a quality improvement project in 2008. Fourteen BHPs (48% of providers in a regional VA network) agreed to participate in a 30-minute, semi-structured phone interview. The interview included questions about their perceived role as a CCC provider, depiction of usual practice styles and behaviors, and perceptions of typical barriers and facilitators to providing behavioral healthcare to Veterans in CCC. Interviews were transcribed verbatim into a text database and analyzed using grounded theory. Results Six main categories emerged from the analysis: (a) Working in the VA Context, (b) Managing Access to Care on the Front Line, (c) Assessing a Care Trajectory, (d) Developing a Local Integrated Model, (e) Working in Collaborative Teams, and (f) Being a Behavioral Health Generalist. These categories pointed to system, clinic, and provider level factors that impacted BHP's role and ability to implement CCC. Across categories, participants identified ways in which they provided Veteran-centered care within variable environments. Conclusions This study provided a contextualized account of the experiences of BHP's in CCC. Results suggest that these providers play a multifaceted role in delivering clinical services to Veterans while also acting as an interdependent component of the larger VA behavioral health and primary care systems. Based on the inherent challenges of enacting this role, BHPs in CCC may benefit from additional implementation support in their effort to promote health care integration and to increase access to patient-centered care in their local clinics.